Governance in Application-Based (Online) Transportation Innovation Policies in Indonesia in the Disruption Era - Setiawan, Muhamad Ari; Salomo, Roy Valiant; Kurniawan, Teguh (Advances in Social Sciences Research Journal, 2023)
Transportation is even considered a hero in conditions of public transportation infrastructure that the Government has not been able to realise optimally. This is coupled with the contribution made by this new service industry to the economy and many new job opportunities in the informal sector that has helped reduce underemployment in big cities. Hence the importance of strengthening governance in application-based (online) transportation innovation policies in Indonesia in the Era of disruption. This research uses the Management & Policy Network theory from Klijn and Koppenjan (2000) on four indicators: policy networks, policy formulation, intermediate outcomes and conflict management. The research method is in a qualitative post-Potivism approach which will be analysed in depth based on existing phenomena. The results show that governance of the Application-Based (Online) Transportation Innovation policy in Indonesia during the Disruptive Era has not yet been formed. This is because the Management & Policy Network has not shown significance for the reason that there are no basic regulations and formal rules, both technically and non-technically, which emphasise the management of Online Transportation, especially two-wheelers because they are not public transport vehicles or public services, which have a significant accident potential compared to other transportation. Apart from that, an alternative is also provided by researchers, namely the importance of the strength of collaborative leadership in increasing government commitment to making decisions regarding online transportation needed by Indonesian people